2022
DOI: 10.1590/1980-549720220027
|View full text |Cite
|
Sign up to set email alerts
|

Diet quality index and its components have not associated with the development of breast cancer risk assessed by the diet quality index: a case-control study

Abstract: Objective: To investigate if the diet quality and its components are associated with breast cancer risk. Methods: A case-control study was conducted with 332 women, 114 who were diagnosed with breast cancer, and 218 control individuals. Groups were matched for age, body mass index, and menopausal status. The quality of diet was assessed using Brazilian Healthy Eating Index Revised (BHEI-R) and its components. Food consumption was measured through three 24-h dietary recalls and assessed using the NDS-R softwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
0
0
Order By: Relevance
“…However, our results showed that people in the highest tertile compared to the lowest tertile of DQI-I scores had a significantly lower odds of BrCa. Inconsistent with our results, Godoy et al reported no association between the DQI and its components with BrCa risk [31].…”
Section: Discussionsupporting
confidence: 78%
“…However, our results showed that people in the highest tertile compared to the lowest tertile of DQI-I scores had a significantly lower odds of BrCa. Inconsistent with our results, Godoy et al reported no association between the DQI and its components with BrCa risk [31].…”
Section: Discussionsupporting
confidence: 78%